Pelatihan Perancangan Shelter Kucing Jalanan dengan Metode Biomimikri dan English for Public Awareness Campaign - Alexander Adrian Saragi; Margaret Stevani; Fitri Rahmawati Nasution; Nurfaizah Marwan; Mentari Septanya Sitorus (LPPM Universitas Harapan Bangsa Purwokerto, 2026)
ABSTRACT This community service program aimed to enhance students’ capacity to design shelters for stray cats through a biomimicry approach while also strengthening their public communication competence through an English for Public Awareness Campaign. The activity was conducted at Universitas Negeri Makassar and utilized the digital design technology Autodesk Fusion 360 to produce shelter models that were adaptive to urban environments and the natural behavioral needs of cats. The implementation methods included biomimetic design training, three-dimensional modeling practice, and the development of public awareness campaigns using academic English aligned with the terminology of the Sustainable Development Goals (SDGs). The results showed an improvement in students’ understanding of nature-based design principles, their ability to use design software, and their skills in constructing factual and diplomatic English narratives for public awareness campaigns. The program also encouraged the integration of design innovation, international language literacy, and community participation in efforts to improve urban animal welfare and public environmental awareness. Keywords : Design training, stray cat shelter, biomimicry, english for public awareness campaign ABSTRAK Program pengabdian masyarakat ini bertujuan meningkatkan kapasitas mahasiswa dalam merancang shelter kucing jalanan melalui pendekatan biomimikri serta memperkuat kompetensi komunikasi publik melalui English for Public Awareness Campaign. Kegiatan dilaksanakan di Universitas Negeri Makassar dengan memanfaatkan teknologi desain digital Autodesk Fusion 360 untuk menghasilkan model shelter yang adaptif terhadap lingkungan perkotaan dan kebutuhan perilaku alami kucing. Metode pelaksanaan meliputi pelatihan desain biomimetik, praktik pemodelan tiga dimensi, serta penyusunan kampanye kesadaran publik berbasis bahasa Inggris akademik yang selaras dengan terminologi Sustainable Development Goals (SDGs). Hasil kegiatan menunjukkan peningkatan pemahaman mahasiswa terhadap prinsip desain berbasis alam, kemampuan penggunaan perangkat lunak desain, serta keterampilan menyusun narasi kampanye publik Bahasa Inggris yang faktual dan diplomatis. Program ini juga mendorong integrasi antara inovasi desain, literasi bahasa internasional, dan partisipasi komunitas dalam upaya meningkatkan kesejahteraan hewan perkotaan serta kesadaran lingkungan masyarakat. Kata kunci : Pelatihan perancangan, shelter kucing jalanan, biomimikri, kampanye kesadaran publik berbahasa inggris